A Patron to Forget: Giovanni Aurelio Augurello (1441–1524) and Doge Agostino Barbarigo (1419–1501) - Soranzo, Matteo (Quaderni d'Italianistica)

(untitled) (Iter Press, 2023)
The article examines a Latin encomiastic poem by Giovanni Aurelio Augurello (1441–1526), preserved in two published versions that display notable differences. These variations include the poem’s dedication to doge Agostino Barbarigo (1419–1501), the account of events related to Charles VIII’s Italian campaign, and the characterization of the French army. By comparing these versions and analysing key passages, the article hypotesises how and why Augurello revised his text to adapt it to the historical, social and political changes occurring in late 15th and early 16th Venice.